2014
DOI: 10.1002/symb.105
|View full text |Cite
|
Sign up to set email alerts
|

“Why Would Our Heavenly Father Do that to Anyone”: Oppressive Othering through Sexual Classification Schemes in the Church of Jesus Christ of Latter‐Day Saints

Abstract: In this article, we examine how leaders of The Church of Jesus Christ of Latter-Day Saints (LDS or LDS Church) responded to the emergence of homosexuality as a prominent social issue by engaging in "oppressive othering" (Schwalbe et al. 2000), which refers to the process whereby elites classify members of other groups as morally inferior. On the basis of LDS archival materials, we analyze how LDS elites accomplished "oppressive othering" by constructing sexual classification schemes defining homosexuality as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
(71 reference statements)
0
30
0
Order By: Relevance
“…Whereas investigations typically focus on the use of racial, classed, gendered, or sexual beliefs to accomplish othering, my findings suggest that religious identities may also be used to differentiate privileged social locations from unwanted ones (see also McQueeney 2009;Sumerau, 2014;Wilkins 2008 for the use of religion to "other" groups). Similar to African-American men who claimed masculine privileges by denigrating the efforts of women during the Civil Rights movement (Collins 2005 for a review of this American history), or heterosexual women rugby players who claimed respectable feminine identities by denigrating lesbian women (Ezzell 2009 for such examples), the LGBT Christians I studied claimed religious privilege by denigrating non-religious people.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Whereas investigations typically focus on the use of racial, classed, gendered, or sexual beliefs to accomplish othering, my findings suggest that religious identities may also be used to differentiate privileged social locations from unwanted ones (see also McQueeney 2009;Sumerau, 2014;Wilkins 2008 for the use of religion to "other" groups). Similar to African-American men who claimed masculine privileges by denigrating the efforts of women during the Civil Rights movement (Collins 2005 for a review of this American history), or heterosexual women rugby players who claimed respectable feminine identities by denigrating lesbian women (Ezzell 2009 for such examples), the LGBT Christians I studied claimed religious privilege by denigrating non-religious people.…”
Section: Resultsmentioning
confidence: 80%
“…You need to realize that God still loves you, and so we'll talk about it." In order to manage these interactions, I accepted them as -especially after witnessing similar interactions with visitors to the church -part of the process whereby church members responded to nonreligion in their presence (see also Sumerau 2014), and took detailed notes about each experience.…”
Section: Setting and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, their incorporation of ''treatment'' into their continued calls for pornographic abstinence since the early 1990s also mirrors shifts in conservative Christian sexual education movements and programs (Fields, 2008) as well as their own responses to homosexuality during this time (Sumerau and Cragun, 2014a). In the former case, abstinence-only movements have increasingly recognized the tendency for abstinence-only lessons to fail, and in so doing offered ways people may reclaim their moral standing (and in some cases their symbolic virginity or purity).…”
Section: Seeking Spiritual Treatmentmentioning
confidence: 93%
“…Considering that researchers have noted widespread expansion of pornography throughout American society in recent years (Attwood, 2011) as well as increased rates of religious exiting (i.e., apostasy) from the Mormon Church since 1989 (see Phillips and Cragun, 2013), LDS leaders could be responding to potential failings of their other lessons regarding sexual morals. Even if this were the case, however, increased religious exiting among Mormons is likely due to multiple social factors including but not limited to other sexual (see Sumerau and Cragun, 2014a) and gender (see Sumerau and Cragun, 2014b) conflicts taking place within the church over the last decade. On the other hand, research has shown that overall religious affiliation in the USA has also been declining in recent years (Funk and Smith, 2012) and that pornographic expansion has occurred throughout the world over the last 40 years (Ezzell, 2008), which means they could simply be responding to broader religious and sexual patterns taking place throughout the entirety of the years captured in our data.…”
Section: Seeking Spiritual Treatmentmentioning
confidence: 95%